The Potential of Cabbage (Brassica oleracea var. capitata L.) Rhizosphere Bacteria as Bioremediator of Paraquat Dichloride-Contaminated Soil - Nawangsih, Handani; Aini, Luqman Qurata (University of Brawijaya, 2026)
Weeds are plants that inhibit crop growth, development, and productivity. This leads farmers to use pesticides to control them. Herbicides, such as paraquat dichloride, are commonly used by farmers to control weeds. The U.S. Environmental Protection Agency (EPA) reported that 14 out of 41 commonly used pesticides in horticultural commodities are classified as carcinogenic compounds, and pesticide residues have been reported to contaminate 83% of the observed horticultural crops. Therefore, there is a need for technologies to address the issue of pesticide residues, such as bioremediation. The objective of this study was to determine the potential of bacteria in the cabbage rhizosphere, which is rich in diversity, as a bioremediator for maize fields contaminated with paraquat dichloride. The study was conducted at the Department of Plant Pest and Disease Laboratory, Brawijaya University, and farmers' cabbage fields from December 2019 to December 2020. The experimental design was a randomized block design (RBD) with 3 replications and 10 treatments, including a control group without bacteria or herbicide. The results showed that there were eight isolates showed bioremediation potential, and one isolate showed the best performance.